COVID-19 and Juvenile Probation: A Qualitative Examination of Emergent Challenges and Useful Strategies - Lockwood, Ashley (Criminal justice and behavior, 2023)
The emergence of COVID-19 placed immediate pressure on the juvenile justice system to adapt to changes in case processing and decision-making practices. Juvenile probation agencies were tasked with quickly altering their policies and practice to abide by local public health measures. As probation supervision is the most common disposition in the juvenile justice system, there is both an empirical and practical need to understand the impact that COVID-19 has on a variety of issues surrounding the supervision and provision of services for juveniles. Using self-report survey data from juvenile probation directors across the United States, the current study examines (a) the biggest challenges faced by juvenile probation agencies during the pandemic, (b) the strategies implemented in response to these challenges, and (c) the most pressing issues currently facing the field of juvenile community corrections. Results have the potential to inform future agency decision-making when adjusting juvenile probation policy and practice.